Fotografia w badaniach nad stygmą społeczną. Wnioski metodologiczne z badań nad stygmatyzacją osób, które popełniły przestępstwo - Chomczyński, Piotr (Studia Edukacyjne, 2020)
The goal of this paper is to present some preliminary methodological conclusions from research on social stigmatization of people who served time in prisons. It mainly discusses some patterns that underlie the process of photography interpretation made by interviewees within the techniques of in-depth interview and focus group interview. To characterize the research tools, contexts and circumstances of research are indicated which are important for the understanding of the outcomes obtained. The results are based on an analysis of forty in-depth interviews and eight focus group interview sessions.As this article is methodological in character, the problem of stigmatization as a subject of social rese-arch is only indicated as a context of the analyses presented in this paper.